Comparison of inhaled versus intravenous anesthesia for laryngoscopy and laryngeal electromyography in a rat model - M. Gazzaz; J. Saini; S. Pagliardini; B. Tsui; C. Jeffery; H. El-Hakim (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Propofol and remifentanil intravenous combination is one popular form of total intravenous anesthesia (TIVA) in mainstream clinical practice, but it has rarely been applied to a rat model for laryngoscopy and laryngeal electromyography (LEMG). Our objective was to establish a safe and reproducible general anesthetic protocol for laryngoscopy and endoscopic LEMG in a rat model. Our hypothesis is that TIVA allows a minimally morbid, and feasible laryngoscopy and LEMG. Methods Sprague Dawley rats were subjected to either inhalational anesthesia (IA) (isoflurane) or TIVA (propofol and remifentanil) and underwent laryngoscopy and LEMG. The primary outcome was a complete minimally interrupted rigid laryngoscopy and obtaining reproducible motor unit potentials from the posterior cricoarytenoid muscles. The secondary outcome was morbidity and mortality. Results Seventeen out of twenty-two rats underwent both TIVA and IA. Only two underwent IA only. All nineteen rats that underwent IA had a successful experiment. Seventeen rats underwent TIVA, however, only nine completed a successful experiment due to difficulty achieving a surgical plane, and respiratory events. Upon comparing the success of the two anaesthetic regimens, IA was superior to TIVA (P = 0.0008). There was no statistical difference between the amplitudes (p = 0.1985) or motor units burst duration (p = 0.82605) of both methods. Three mortalities were encountered, one of which was due to lidocaine toxicity and two were during anesthetic induction. Respiratory related morbidity was encountered in two rats, all seen with TIVA. Conclusions TIVA is not an ideal anesthetic regimen for laryngeal endoscopy and LEMG in rat models. Contrary to our hypothesis, IA did not affect the quality of the LEMG and allowed a seamless rigid endoscopy.